Score on Coma Recovery Scale-Revised at admission predicts outcome at discharge in intensive rehabilitation after severe brain injury. (12th May 2018) - Portaccio, Emilio; Morrocchesi, Azzurra; Romoli, Anna Maria; Hakiki, Bahia; Taglioli, Maria Pia; Lippi, Elena; Di Renzone, Martina; Grippo, Antonello; Macchi, Claudio
ABSTRACT: Objective : To assess the prognostic utility of the Coma Recovery Scale-Revised (CRS-R) in rehabilitation of patients surviving from severe brain injury. Methods : In this prospective cohort study, all patients consecutively admitted to an Italian Intensive Rehabilitation Unit, with a diagnosis of unresponsive wakefulness syndrome (UWS) or minimally conscious state (MCS) due to acquired brain injury, underwent clinical evaluations using the Italian version of the CRS-R. At discharge, patients transitioning from UWS to MCS or emergence from MCS (E-MCS) and from MCS to E-MCS were classified as improved responsiveness (IR). Score on the Glasgow Outcome Scale (GOS) at discharge was recorded. Results : In total, 137 (66 UWS, 71 MCS) subjects were enrolled. After a mean hospital stay of 5.3 ± 2.9 months, 81 (59.1%) patients achieved an IR. In the multivariable analysis, IR was associated with higher CRS-R score at admission ( p  = 0.002) and younger age at injury ( p  = 0.010). Moreover, higher GOS scores at discharge were related to younger age at injury ( p  = 0.018), shorter time post-onset ( p  = 0.003) and higher CRS-R score at admission ( p  < 0.001). Conclusions : Higher CRS-R scores at admission in intensive rehabilitation unit can help differentiate patients with better outcome at discharge, providing information for rehabilitation planning and communication with patients and their caregivers.